Expression and Possible Role of Nicotinic Acetylcholine Receptor ε Subunit (AChRe) in Mouse Sperm - Makino, Yusei (Biology (Basel), 2021)
SIMPLE SUMMARY: Numerous neurotransmitters have been reported to affect mammalian sperm function and are thought to play an important role in the phenomenon of fertilization. This study focused on acetylcholine (ACh) and its receptor subunit, the ε subunit (AChRe), and analyzed the effect of ACh and AChRe on mammalian sperm function and fertilization. The present study revealed the localization of AChRe in the murine testes and spermatozoa, and showed that acrosome reaction (AR), an important change in sperm function associated with fertilization, is suppressed by ACh. Furthermore, this suppressing effect was significantly inhibited by an AChRe specific antagonist, suggesting that AChRe play as a regulator of mammalian sperm AR. These results may aid in further elucidating the phenomenon of mammalian sperm function for fertilization by ACh and in the establishment of a new method of superior sperm selection via AChRe. ABSTRACT: The nicotinic acetylcholine receptor (nAChR) is one of the receptors of acetylcholine (ACh), and nicotine (NIC) acts as an agonist of this receptor. Among the nAChR subunits, we found that the ε subunit (AChRe) had approximately 10 to 1000 times higher level of mRNA expression in mouse testes than the other subunits. In this study, we aimed to elucidate the expression and localization of AChRe in the testes and spermatozoa of mice and clarify the effect of AChRe on sperm function. Immunocytochemistry showed that AChRe was expressed in the murine testes and spermatozoa. We found that AChRe was localized only in elongated spermatids from step 12 onwards in the testes. In spermatozoa, AChRe was localized in the head, especially in the anterior region of the acrosome, but only approximately 50% of spermatozoa showed this immunoreactivity. Additionally, we analyzed the effects of ACh and NIC on sperm acrosome reaction (AR) and found that both ACh and NIC suppressed the AR rate, which was restored by an AChRe-specific antagonist. These results suggest that AChRe may be a regulator of mammalian sperm AR.